Integral Roles for Integrins in γδ T Cell Function - Siegers, Gabrielle M. (Frontiers in Immunology, 2018)
Integrins are adhesion receptors on the cell surface that enable cells to respond to their environment. Most integrins are heterodimers, comprising α and β type I transmembrane glycoprotein chains with large extracellular domains and short cytoplasmic tails. Integrins deliver signals through multiprotein complexes at the cell surface, which interact with cytoskeletal and signaling proteins to influence gene expression, cell proliferation, morphology and migration. Integrin expression on γδ T cells (γδTc) has not been systematically investigated; however, reports in the literature dating back to the early 1990s reveal an understated role for integrins in γδTc function. Over the years, integrins have been investigated on resting and/or activated peripheral blood-derived polyclonal γδTc, γδTc clones as well as γδ T intraepithelial lymphocytes. Differences in integrin expression have been found between αβ T cells (αβTc) and γδTc, as well as between Vδ1 and Vδ2 γδTc. While most studies have focused on human γδTc, research has also been carried out in mouse and bovine models. Roles attributed to γδTc integrins include adhesion, signaling, activation, migration, tissue localization, tissue retention, cell spreading, cytokine secretion, tumour infiltration and involvement in tumour cell killing. This review attempts to encompass all reports of integrins expressed on γδTc published prior to December 2017, highlights areas warranting further investigation, and discusses the relevance of integrin expression for γδTc function.